2018
DOI: 10.7717/peerj.4603
|View full text |Cite
|
Sign up to set email alerts
|

PredictingPinus monophyllaforest cover in the Baja California Desert by remote sensing

Abstract: The Californian single-leaf pinyon (Pinus monophylla var. californiarum), a subspecies of the single-leaf pinyon (the world’s only one-needled pine), inhabits semi-arid zones of the Mojave Desert (southern Nevada and southeastern California, US) and also of northern Baja California (Mexico). This tree is distributed as a relict subspecies, at elevations of between 1,010 and 1,631 m in the geographically isolated arid Sierra La Asamblea, an area characterized by mean annual precipitation levels of between 184 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Much research has focused on time series analyses of desertification or forest decline (Peters et al [66], Joshi et al [67], and more recently Dorman et al [68], Bajocco et al [69], Fensholt et al [70], and Zhang et al [71]). Remote sensing data has aided research in tracking the health and distribution of certain species of vegetation (Escobar-Flores et al [72], Pham et al [4], Paz-Kagan et al [5]). Yet, again, all of the above employed additional spectral bands.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on time series analyses of desertification or forest decline (Peters et al [66], Joshi et al [67], and more recently Dorman et al [68], Bajocco et al [69], Fensholt et al [70], and Zhang et al [71]). Remote sensing data has aided research in tracking the health and distribution of certain species of vegetation (Escobar-Flores et al [72], Pham et al [4], Paz-Kagan et al [5]). Yet, again, all of the above employed additional spectral bands.…”
Section: Discussionmentioning
confidence: 99%
“…Another big advantage of this mission is the wide swath of 290 km (more than 100 km wider than the Landsat satellite), which makes it an ideal sensor for forest analyses over a large area at the regional and national scales. A few studies have focused on the use of the Sentinel-2 data for the classification of tree type and tree species [26,[29][30][31][32][33]. Wessel et al [30] analysed the separation of beech from oak trees in a managed forest in Bavaria.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of people in Shanxi Province, Inner Mongolia, and parts of Beijing and Tianjin cities and Hebei Province in North China has suffered from the destruction of the ecological environment and the scarcity of water resources resulting from conditions of almost continuous drought. Given that the Inner Mongolian Plateau is the primary ecological barrier of Inner Mongolia and the Beijing-Tianjin-Hebei region, for those who rely on this barrier, the methods used by the Government of China to protect the ecological environment and water resources on the plateau will have a significant impact on the effectiveness of the ecological barrier of the region (Miao et al, 2015; Escobar-Flores et al, 2018). Many studies have reported that China’s large-scale water resource protection plans and water transport projects will significantly affect the ecological environment and available water resources in the Inner Mongolian Plateau and the Beijing-Tianjin-Hebei region.…”
Section: Introductionmentioning
confidence: 99%